Effectiveness of The Use of Augmented Reality Based Learning Media in Solid Figure Material - Karim; Hanna Syajida; Rahmita Noorbaiti (Universitas Ahmad Dahlan, 2025)
The lack of understanding of mathematical concepts among junior high school students regarding spatial geometry is often due to difficulties in visualizing these objects. Augmented Reality (AR) technology can be utilized as a learning tool to facilitate the learning process, particularly for abstract mathematical concepts like spatial geometry. This research aimed to determine the effectiveness and student response towards the implementation of AR-based learning media in understanding the concepts of spatial geometry among eighth-grade students in junior high school level. The study employs a Quasi-experimental method with a Nonequivalent control group design. The population of this research is the eighth-grade students at SMPN 24 Banjarmasin. Purposive sampling technique is used for sample selection. Research instruments include pre-tests, post-tests, and questionnaires. Data analysis techniques for the tests involve using t-tests and N-Gain tests, while non-test data analysis is conducted using quantitative descriptive data analysis. The research results are as follows: (1) Based on the t-test, there is a significant difference in learning outcomes between students using AR-based learning media compared to those who did not receive such treatment. Furthermore, based on the N-Gain test, the average score for the experimental group is 0.58, categorized as effective, whereas the control group scored 0.15, categorized as less effective. 2) The percentage of questionnaire responses from students regarding the implementation of AR-based learning media for spatial geometry is categorized as good, at 79%. In conclusion, the utilization of AR-based learning media proves to be effective in enhancing students' understanding of spatial geometry concepts in mathematics lessons for eighth-grade students.